Interview with Professor Dr. Govinda Raj Pokharel - Thanju, Jeewan Parsad (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Avaiable DOI: http://dx.doi.org/10.3126/hn.v13i0.10062 HYDRO NEPAL Journal of Water, Energy and Environment Issue No.13, July 2013 Page: 78-80 Uploaded Date:2014-03-14